DEVELOPMENT AND INVESTIGATION OF NEW DESIGN PIEZOELECTRIC LASER BEAM SHUTTER - A. Bubulis; V. Jurenas; V. Maciukiene; S. Navickaite (Приборы и методы измерений)
In this paper authors investigate laser beam shutting system of a new design. The scheme of the investigated laser beam shutter and working principle are explained. According the experimental research results of the developed laser beam shutting system was performed.